Einstein (Boston, Mass. : WBGH Educational Foundation, 1979)
Presents a detailed account of the life and times of Albert Einstein through photographs, film clips, and the scientist's published writings. Shows the great social and political forces that dominated so much of Einstein's personal life and professional career
laser disc format
Keywords: Einstein, Albert, -- 1879-1955; Physicists -- Biography